Psychiatry: Personality Disorder - Team-based learning module - Ruth Levine (Association of American Medical Colleges, 2005)
Abstract Introduction This team-based learning session was designed to instruct psychiatry clerkship students in the recognition and management of personality disorders. Methods Students are required to read Chapter 8: Personality Disorders of the book "Psychiatry" by Janis Cutler, in advance. The session included here is a 2-hour session facilitated by a physician, which was part of a series of approximately 16 teaching sessions with clerkship students. Results Converting the lecture format to team learning sessions earned a positive response from students and an improvement in test scores. In a 6-week clerkship using team-based learning, students in the team learning cohort performed better on the NBME psychiatry shelf exam (p = 0.004), and were more receptive to working in teams than historical control subjects. Discussion The team learning sessions were demonstrated to be effective through both student reaction and test scores. Although there were correct answers to the questions in the application-focused exercise, students often chose acceptable alternatives. It is recommended that the application be used for learning, and not for grading purposes.